DESIGN OF INDOOR AGARIC CULTIVATION MONITORING DEVICE BASED ON INTERNET OF THINGS AND EMOTIONAL BEHAVIOR CHANGE - Long, Guangli (The international journal of neuropsychopharmacology, 2022)
Abstract Background Auricularia auricula grows in high environmental conditions and takes a long time to produce. The environmental quality control of Auricularia auricula has gradually become the biggest bottleneck and obstacle restricting its quality production. At present, the environmental control of most edible fungi still depends on artificial experience. The control and regulation efficiency of environment and nutrient solution is low, prone to deviation, unable to provide a comprehensive and high-quality growth environment for edible fungi, which seriously affects its production efficiency and hinders its large-scale development. Therefore, in order to create the best environmental conditions for the growth and development of Auricularia auricula and improve the quality, yield and economic value of Auricularia auricula products, it is particularly important to introduce the Internet of things technology into indoor Auricularia auricula cultivation monitoring from the perspective of cognitive psychology to control the environmental parameters of Auricularia auricula cultivation. Based on cognitive psychology and emotional behavior changes, the cultivation system of Auricularia auricula was improved accordingly. Subjects and Methods From the perspective of cognitive psychology, an indoor agaric cultivation monitoring device based on Internet of things is designed, which is mainly composed of monitoring terminal (stm32f103zet6 microcomputer as the main controller), cloud platform and user control center. The monitoring terminal is mainly responsible for sensor data acquisition, threshold setting and control of some external equipment, including fan cooling, lighting, grass curtain ventilation, water pump watering and infrared anti-theft alarm control; The cloud platform mainly receives various data information uploaded by the main controller through wireless data communication technology and sends it to users; The user control center is mainly responsible for real-time remote monitoring of the growth environment of Auricularia auricula through mobile phones or computers. The information collected by each sensor is automatically identified and tracked in real time after being processed by single chip microcomputer. The data is displayed in real time through LCD, and the data is uploaded to onenet cloud platform through NB IOT wireless communication technology, so as to realize accurate and fast data interactive transmission, remote monitoring and report the real-time status to users. On the other hand, the alarm effect is achieved by setting the corresponding threshold, and the corresponding decision-making and control are carried out automatically. SPSS 22.0 software is also used for data statistical analysis. The measurement data is expressed as mean ± standard deviation (x ± s). The statistical method is: descriptive statistics is used for general data characteristics, t-test is used for the comparison of the mean of two independent samples, nonparametric Kruskal Wallis test is used for ordered classified data, and regression analysis is used to verify the mediation effect of RS between as and terminal according to the mediation effect test model. P < 0.05 was statistically significant. Results Compile and download the software and assemble the module, process the environmental parameters collected by the sensor through the microcomputer, and send the sensor data to the onenet cloud platform through the Nb Internet of things module. Users can remotely monitor data through computer or mobile phone to realize the functions of data detection, threshold setting, data display, audible and visual alarm, parameter adjustment, cloud platform monitoring and so on., The total score of Internet of things terminal as is different in whether to monitor the environment (P < 0.05), and the total score of RS is different in users' use of cloud platform data (P < 0.05), that is, the terminal running with emotional behavior changes performs better; The total score of SCL-90 was only different in use. Conclusion The indoor agaric cultivation monitoring device based on Internet of things and cognitive psychology adopts NB IOT wireless data communication module for wireless transmission, which can complete the collection of indoor environmental information and display the information on mobile phones and computers. It has the functions of remote monitoring and anti-theft alarm, and can realize the intelligent management of agaric cultivation. At the same time, it can also promote the application of cognitive psychology of the Internet of things in various fields and achieve good social builders, managers and collaborators. Acknowledgements Supported by a project grant from Ministry of education industry university cooperation collaborative education project, (Grant No. 202102371060).